Aflatoxin M1 contaminations in mouldy cheese - Ezgi Özgören (Mljekarstvo, 2016)
In this study, a total of 100 mouldy cheese samples were collected from randomly selected markets from 5 different cities of Turkey during October and November. Samples were analyzed for aflatoxin M1 by using enzyme linked immunosorbent assay (ELISA) technique. Aflatoxin M1 was detected in 52 samples and their levels ranged from 10.6 to 702 ng/kg. The widespread presences of aflatoxin M1 in mouldy cheese may be considered to be potential hazards for human health.